Medically Assisted Reproduction and Birth Outcomes: A Within-Family Analysis Using Finnish Population Registers. Issue 8 (August 2019) - Goisis, Alice; Remes, Hanna; Martikainen, Pekka; Klemetti, Reija; Myrskylä, Mikko
Abstract : (Abstracted from Lancet 2019;393:1225–1232) Medically assisted reproduction—that is, reproduction brought about through treatments such as ovulation induction, artificial insemination, in vitro fertilization (IVF), or intracytoplasmic sperm injection with fresh or frozen embryo transfer—has resulted in the birth of more than 5 million children. Although previous studies have consistently found that children born after medically assisted reproduction have worse perinatal outcomes than do children who were conceived naturally, the mechanisms underlying this association are not fully understood.